Pain and Nausea Intensity, Social Function, and Psychological Well-Being among Women with Metastatic Breast Cancer - Ryan R. Senkpeil PhD; Julie S. Olson PhD; Erica E. Fortune PhD; Alexandra K. Zaleta PhD (Journal of Patient Experience, 2022)
Advances in diagnostics and therapeutics have improved prognosis for metastatic breast cancer (MBC). Yet, treatment and disease burden—including experiences of pain and nausea—present practical and emotional challenges. To better support patients and enhance quality of life, deeper understanding of the pathways linking physical and psychological health is needed. To this end, we examined associations of pain and nausea with depression and anxiety among women with MBC. In doing so, we highlighted social function as a potentially important mechanism in this relationship. This observational, cross-sectional study included 148 predominantly non-Hispanic White, highly educated women living with MBC. Multivariate regression models demonstrated that more intense pain and nausea were significantly associated with higher levels of depression and anxiety ( p  < .001). Causal mediation analyses confirmed significant indirect effects whereby decreases in social function associated with pain and nausea contributed to depression and anxiety. Thus, our findings illustrate decreased social function as one pathway through which pain and nausea contribute to escalation of depression and anxiety. Our results, therefore, underscore the importance of supporting social function among women with MBC to potentially reduce psychological sequelae of pain and nausea.